Application of a Holed Cathode and Anode Prepared with a Picosecond Pulsed Laser for Lithium Ion Batteries (1) Performance of Holed Cathodes with Solid-State Electrolytes . (25th June 2020) - Watanabe, Tatsuya; Gunji, Takao; Suzuki, Kei; Ando, Nobuo; Nakamura, Susumu; Hayashi, Narumi; Soma, Naohiko; Matsumoto, Futoshi
Abstract : The design of the interface between the electrode and electrolyte is very important and should be carefully considered during the development of lithium-ion batteries (LIBs) with a high rate performance; this is especially true for all-solid-state LIBs. Recently, we developed a structure with holes fabricated with a picosecond pulsed laser and showed an improvement in the rate performance of a holed cathode in liquid electrolyte-based LIBs. In this study, a holed structure was applied to solid-state electrolytes (SSEs), such as Li1+x+y Alx Ti2-x Siy P3-y O12 (LATP) and poly(ethylene oxide)(PEO)/lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The filling of SSE particles instead of a conventional liquid electrolyte into the holes on the cathode produced a high rate performance, indicating that the advantage of a holed structure could be applied to all-solid-state LIBs.